The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep35768
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Thin B doped g-C3N4 Nanosheets: High-Temperature Ferromagnetism and calculated Half-Metallicity

Abstract: Since the graphitic carbon nitride (g-C4N3), which can be seen as C-doped graphitic-C3N4 (g-C3N4), was reported to display ferromagnetic ground state and intrinsic half-metallicity (Du et al., PRL,108,197207,2012), it has attracted numerous research interest to tune the electronic structure and magnetic properties of g-C3N4 due to their potential applications in spintronic devices. In this paper, we reported the experimentally achieving of high temperature ferromagnetism in metal-free ultrathin g-C3N4 nanoshee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 46 publications
(43 reference statements)
2
64
0
1
Order By: Relevance
“…In particular, our group has reported that size-tailored, uniformed carbon spheres can promote GCN toward enhanced photocatalysis [32]. Meanwhile, non-metal doping is demonstrated as an effective approach since the electronic structure and band gap would be changed dramatically via heteroatom doping [17,33,34]. Nitrogen-doped carbonaceous nanomaterials are found to be able to expedite the migration of photoinduced electron-hole pairs and promote the generation of active sites during the photocatalytic reaction by forming delocalized pi bonds [22,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our group has reported that size-tailored, uniformed carbon spheres can promote GCN toward enhanced photocatalysis [32]. Meanwhile, non-metal doping is demonstrated as an effective approach since the electronic structure and band gap would be changed dramatically via heteroatom doping [17,33,34]. Nitrogen-doped carbonaceous nanomaterials are found to be able to expedite the migration of photoinduced electron-hole pairs and promote the generation of active sites during the photocatalytic reaction by forming delocalized pi bonds [22,[35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Some intrinsic characteristics, such as small specic surface area and rapid recombination of the photogenerated electronhole pair, restrict its application. Accordingly, many strategies have been adopted to improve the photocatalytic performance of g-C 3 N 4 by means of the fabrication of nano/mesoporous structures with a so or hard template, [4][5][6] a heterojunction with other semiconductors, [7][8][9][10][11] coupling with metal particles, [12][13][14][15][16][17][18][19] and metal or non-metal doping, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] etc. Among these methods, doping with nonmetal elements showed great possibility to enhance the visible light photocatalysis of g-C 3 N 4 , since the electronic structure and band gap changed dramatically via atomic doping.…”
Section: Introductionmentioning
confidence: 99%
“…20 Carbon and nitrogen self-doped g-C 3 N 4 exhibited improved photoreactivity by forming delocalized p bonds to increase visible light absorption and electric conductivity. 20,21 Many nonmetal heteroatoms, such as B, [21][22][23][24] P, [25][26][27][28] S, [29][30][31][32][33][34][35][36] O, [37][38][39] were introduced to improve the visible light photocatalytic activities for hydrogen generation and organic degradation compared with pristine g-C 3 N 4 . Experimental and theoretical studies showed that the dopants tune the electronic structure by forming localized states in the band gap, facilitating the transfer of photogenerated electron hole pairs.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated Curie temperature is approximately 297 K for the holey planar C N @C 2 N system. Previous theoretical and experimental reports suggest that doped carbon nitride based systems show Curie temperatures in a similar range. Superconducting quantum interference devices (SQUIDs) are used to calculate the Curie temperature experimentally.…”
Section: Resultsmentioning
confidence: 73%
“…Previous theoretical and experimental reports suggest that doped carbon nitride based systems show Curie temperatures in a similar range. Superconducting quantum interference devices (SQUIDs) are used to calculate the Curie temperature experimentally. Correspondingly, Monte Carlo (MC) simulations were performed to estimate the Curie temperature ( T C ) of the planar C N @C 2 N system .…”
Section: Resultsmentioning
confidence: 73%